The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18632/oncotarget.17391
|View full text |Cite
|
Sign up to set email alerts
|

Increased S100A15 expression and decreased DNA methylation of its gene promoter are involved in high metastasis potential and poor outcome of lung adenocarcinoma

Abstract: PurposeThis study aims to determine the functional role of S100A15 and its promoter DNA methylation patterns in lung cancer progression.Experimental DesignWe analyzed 178 formalin-fixed paraffin embedded specimens from lung cancer patients, including 24 early stage and 91 advanced stage adenocarcinoma. S100A15 protein expression was evaluated by immunohistochemistry stain, and its DNA methylation levels were measured by pyrosequencing.ResultsS100A15 nuclear staining was increased in lung adenocarcinoma patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
(37 reference statements)
1
9
0
Order By: Relevance
“… 36 In contrast to hypermethylation, increased expression of S100A15 and reduced DNA methylation of its gene promoter have also been proved to be associated with high metastatic potential and poor prognosis of LUAD. 37 In this study, we demonstrated that the AGR2 promoter region was hypomethylated and AGR2 was highly expressed in LUAD cells through bioinformatics analysis and molecular experiments, which was consistent with studies of AGR2 promoter methylation in other cancers. Sung HY et al found that the promoter of AGR2 is hypomethylated and AGR2 is highly expressed in ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“… 36 In contrast to hypermethylation, increased expression of S100A15 and reduced DNA methylation of its gene promoter have also been proved to be associated with high metastatic potential and poor prognosis of LUAD. 37 In this study, we demonstrated that the AGR2 promoter region was hypomethylated and AGR2 was highly expressed in LUAD cells through bioinformatics analysis and molecular experiments, which was consistent with studies of AGR2 promoter methylation in other cancers. Sung HY et al found that the promoter of AGR2 is hypomethylated and AGR2 is highly expressed in ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“…PCNA is a key eukaryotic replication accessory factor that plays an important role in the cell cycle and apoptosis [63]. In addition, PCNA can promote LC progression [64]. CDK1 and CDK2 belong to the cyclin-dependent kinases (CDKs) family.…”
Section: Discussionmentioning
confidence: 99%
“…In LUAD, many studies reported that gene DNA methylation was associated with cancer growth. For example, Chen et al (2017) found that decreased DNA methylation of S100A15 was involved in high metastasis of LUAD. Wang, Lu, Shen, Wu, and Zhao (2014) reported that the SAMHD1 promoter, highly methylated in LUAD, impeded SAMHD1 expression.…”
Section: Discussionmentioning
confidence: 99%